2014
DOI: 10.17267/2238-2704rpf.v4i2.448
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency in the Female Genital Laxity - A Pilot Study

Abstract: Purpose: To evaluate the effect of non-ablative radiofrequency capacitive (RF) in the treatment of sagging skin in the region of labia majora, and the influence on sexual function. Methods: The sample included 9 women with complaints of sagging skin in the labia majora, of which 7 had sexually active. The protocol consisted of 8 sessions of RF, with a temperature of 39 º C to 41 º C, 1x/week for up to 20 minutes. Evaluation tools, photographs taken before the first session and eight days after the last session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
3
1
2
Order By: Relevance
“…Our results suggest that one or two treatments may be sufficient to achieve a very reasonable level of improvement in the treated conditions; however, some patients felt that they would benefit from more than four sessions. The FSFI changes exceeded the results achieved by previous studies (5,8), suggesting the investigated device is a highly efficient modality for treating impeded female sexual function.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Our results suggest that one or two treatments may be sufficient to achieve a very reasonable level of improvement in the treated conditions; however, some patients felt that they would benefit from more than four sessions. The FSFI changes exceeded the results achieved by previous studies (5,8), suggesting the investigated device is a highly efficient modality for treating impeded female sexual function.…”
Section: Discussioncontrasting
confidence: 71%
“…In 2016, a prospective cohort study on 17 women was conducted in Croatia using a monopolar RF device for labial tissue tightening and improvement of labial laxity (5). The investigators reported an average "moderate change" regarding improvement in vulvar appearance.…”
Section: Introductionmentioning
confidence: 99%
“…Our results may indicate that the model of wider area treatment of vulvar tissue, not introitus only that was discussed by Alisond RM as well, is more effective as tightening of labia majora, labia minora and perineum/vestibulum contributes to the positive perception of aesthetic improvement.…”
Section: Discussionmentioning
confidence: 55%
“…A RF trata-se de uma onda eletromagnética e tem seu mecanismo de ação baseado na geração de calor nas camadas cutâneas, com retração imediata do colágeno existente e neocolanogênese ao longo do tempo13. Este recurso tem sido muito utilizado em pacientes com flacidez cutânea de face, tronco e membros, com melhora significativa do quadro 14 , e esta começando a ser utilizado também na região genital 15,16,17 . Um estudo piloto buscou avaliar a segurança da radiofrequência não ablativa em região de grandes lábios, no qual não foi verificado nenhum efeito adverso 17 .…”
Section: Conflitos De Interessesunclassified
“…Este recurso tem sido muito utilizado em pacientes com flacidez cutânea de face, tronco e membros, com melhora significativa do quadro 14 , e esta começando a ser utilizado também na região genital 15,16,17 . Um estudo piloto buscou avaliar a segurança da radiofrequência não ablativa em região de grandes lábios, no qual não foi verificado nenhum efeito adverso 17 . Os estudos que utilizam a radiofrequência não ablativa para frouxidão genital, possuem protocolos diferentes, que variam de acordo com o numero de sessões e o tempo de aplicação.…”
Section: Conflitos De Interessesunclassified